Impacts of Human Resource Management on the Financial Performance of Vietnam Joint Stock Commercial Bank for Industry and Trade - Ha, Van Dung; Nguyen, Quoc Buu; Tran, Hai Nam (Asian Journal of Economics and Empirical Research, 2020)
The aim of this paper is to investigate impacts of human resource management on financial performance of Vietnam Joint Stock Commercial Bank for Industry and Trade (VietinBank). The study employs both qualitative and quantitative methods for analysis. Qualitative method is used to finalize the questionnaire while quantitative method is used to test the research hypotheses via measurement scales, descriptive analysis, EFA analysis, correlation coefficients, and linear regression model. The data is collected from 250 employees working at different branches of VietinBank in Vietnam. The results show that these 7 factors: selection, training, job description, performance appraisal, compensation system, career planning, employee participation have significant impacts on the financial performance of VietinBank.